Complete removal of intraspinal extradural mass with unilateral biportal endoscopy - Wang, Tao; Yu, Hang; Zhao, Shi-bin; Zhu, Bin; Chen, Lei; Jing, Jue-hua; Tian, Da-sheng (Frontiers in Surgery, 2022)
Introduction Unilateral biportal endoscopic (UBE) technique can easily decompress the bony spinal canal and accommodate all open surgical instruments under endoscopic guidance. However, indications and reports of this technique have been limited to degenerative and infectious diseases. Methods We used the UBE technique for decompression and removal extradural mass in 5 patients. Under endoscopic guidance, a unilateral approach was used, and decompression and flavectomy were performed. After decompression, tumor removal was performed using various forceps. We evaluated the technical process of the procedure, the patient’s pre- and postoperative symptoms and operative radiology and pathologic results. Results Postoperative pain and disability improved clinically for all patients. Four patients confirmed as epidural cyst, one patient diagnosed as hemangioma. During follow-up, no recurrence was observed. Conclusions We successfully removed five extradural mass lesions by using a biportal endoscopic posterior approach without complications. The biportal endoscopic approach may have advantages, such as minimizing trauma to the normal structures, magnified endoscopic view, and early recovery after the surgery. Biportal endoscopy may be used as an alternative surgical treatment for symptomatic intraspinal extradural benign lesions.